2013
DOI: 10.1111/zoj.12051
|View full text |Cite
|
Sign up to set email alerts
|

Small snails in a big place: a radiation in the semi-arid rangelands in northern Australia (Eupulmonata, Camaenidae,Nanotrachia gen. nov.)

Abstract: Continuing the revision of the Camaenidae in the Australian Monsoon Tropics, we employed comparative analyses of morphological features (with a focus on shell and penial anatomy) and genetic markers (with a focus on mitochondrial COI and 16S sequences) to address the systematic relationships of land snails from the Victoria River District, Northern Territory, and adjacent East Kimberley (Western Australia). These analyses revealed that the species under study represented the previously undescribed genus Nanotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Generally, the amounts of genetic differentiation between species were comparable with interspecific distances observed in other north-western Australian camaenids, such as >3% (COI and 16S) in Exiligada >4% (16S, Criscione et al, 2012), Rhagada >4% (16S) and >7% (COI) , Setobaudinia >6% (COI) and >9% (16S) (Criscione and Köhler, 2013b), Amplirhagada Iredale, 1933 >8% (COI) and >10% (16S) (Köhler and Johnson, 2012), Nanotrachia >5% (COI) and >3% (16S) (Köhler and Criscione, 2013), Baudinella, >3% (COI) and >4% (16S) Retroterra (Criscione and Köhler, 2014a). In Kimberleytrachia there has been a slight overlap between intra-and interspecific distances as was occasionally also observed in other genera.…”
Section: Species Delimitationsupporting
confidence: 81%
See 2 more Smart Citations
“…Generally, the amounts of genetic differentiation between species were comparable with interspecific distances observed in other north-western Australian camaenids, such as >3% (COI and 16S) in Exiligada >4% (16S, Criscione et al, 2012), Rhagada >4% (16S) and >7% (COI) , Setobaudinia >6% (COI) and >9% (16S) (Criscione and Köhler, 2013b), Amplirhagada Iredale, 1933 >8% (COI) and >10% (16S) (Köhler and Johnson, 2012), Nanotrachia >5% (COI) and >3% (16S) (Köhler and Criscione, 2013), Baudinella, >3% (COI) and >4% (16S) Retroterra (Criscione and Köhler, 2014a). In Kimberleytrachia there has been a slight overlap between intra-and interspecific distances as was occasionally also observed in other genera.…”
Section: Species Delimitationsupporting
confidence: 81%
“…Couper and Hoskin (2008) firstly suggested for lizards that sheltered rock habitats provide environmental conditions similar to rainforests permitting the persistence of rainforest lineages even in areas where rainforests have disappeared. Such lithorefugia have clearly been important for the persistence for several camaenid lineages in drier parts of the Kimberley and even have facilitated their radiation into semi-arid environments, such as on the limestone outcrops of the Victoria Bonaparte bioregion of the East Kimberley (Criscione et al, 2012;Köhler and Criscione, 2013). Accordingly, the survival of K. crawfordi, K. setosa and K. umbonis in inland areas may not exclusively rely on the presence of rainforests.…”
Section: Patterns Of Diversification and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies have revealed that species are indeed best delineated by a combination of morphological (shell, genital anatomy) and molecular evidence (e.g., Criscione et al 2012;Köhler and Criscione 2013b). Accordingly, species have been recognised as distinct if they consistently formed phenotypically and genotypically distinct clusters (Sites and Marshall 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this more xeric area supports lower species richness than more humid areas closer to the coast. Twenty-three genera were described from the East Kimberley and Victoria River District combined (e.g., Solem 1985;Criscione et al 2012;Köhler 2013a, 2013b;Köhler and Criscione 2013b) containing 50-60 species in total. Only three of these genera also occur in the NW Kimberley.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%